Accountability Analysis of Village Fund Allocation Management (ADD) Based on Minister of Home Affairs Regulation No. 20 of 2018 in Kalasey One Village, Mandolang District - Hanna E. C. Pelleng; Jenny Morasa; Peter M. Kapojos (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to evaluate the level of accountability in managing the village fund allocation in Kalasey Satu Village, Mandolang District, starting from the stages of planning, implementation, administration, reporting, and accountability. This study in Kalasey Satu Village employed descriptive qualitative research methods. The data utilized in this study is derived from the Village Revenue and Expenditure Budget. The findings indicate that the management of the village fund allocation in Kalasey Satu Village, Mandolang District demonstrates a high level of accountability across the stages of planning, implementation, administration, reporting, and accountability